Penggunaan Media Video Tutorial untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Menggambar Flora di Kelas VII SMP Negeri 6 Bukittinggi - Rahmi, Lailatul; Pebriyeni, Eliya (Lembaga Yasin AlSys, 2025)
This classroom action research (CAR) was motivated by the low learning outcomes of Grade VII students at SMP Negeri 6 Bukittinggi, particularly in the subject of drawing flora. The main issues identified were students’ low learning motivation and the teacher’s limited use of engaging instructional media. The study was conducted over two cycles, each consisting of two sessions. Data were collected through teacher observation sheets, student observation sheets, and assessments of learning outcomes via written and practical tests. The aim of the study was to improve student learning outcomes through the use of video tutorial media. The results showed a significant improvement: in Cycle I, learning mastery reached 61.29%, which increased to 90.32% in Cycle II. These findings confirm that the use of video tutorial media is effective in enhancing student learning outcomes in flora drawing lessons for Grade VII students at SMP Negeri 6 Bukittinggi in the 2025/2026 academic year.